IB - Panandiker V. A. Pai (ed.) (New Delhi, 2000)
This study is a wrap up volume of a project which was initiated a decade ago to study the problems of governance in Bangladesh, India, Nepal, Pakistan and Sri Lanka.
Keywords: Development administration